The Impact of Vaginal Dilator Use on the Quality of Life in Women Treated with Adjuvant Radiotherapy for Cervical Cancer - Liujuan Shao; Xiaoli Chen; Xiaoyan Zhang; Min Zhu; Peijian Jin; Min Hu (Clinical and Experimental Obstetrics & Gynecology)
Background: The aim of the present study was to evaluate the clinical efficacy of a vaginal dilator in patients with cervical cancer after radiotherapy. Methods: A total of 128 patients with cervical cancer (stages I–III) after radical hysterectomy combined with vaginal lengthening surgery were evaluated between January 2018 and January 2021. All eligible patients were told that their radiotherapy treatment resulted in vaginal stenosis and that vaginal dilators may improve this condition. After the patients were informed of the potential benefits, complications, and alternatives, those who agreed to undergo the vaginal dilator manipulation were assigned into Group A (n = 66), while those who refused were included in Group B (n = 62) and received routine treatment. Vaginal diameter and length were measured during the follow-up period and quality of life changes were determined on the basis of the European Organization for Research and Treatment of Cancer (EORTC) Quality-of-Life questionnaire cervical cancer module (EORT QLQ-CX24). Results: Three patients were lost to follow-up over the course of 14 months, while two patients in Group A refused treatment after radical hysterectomy. A total of 123 cases with cervical cancer were analyzed in the course of the study. The vaginal diameter and length were significantly different between the two groups during the follow-up period. Sexual/vaginal function, sexual worry, sexual activity, and sexual enjoyment were also significantly different after radiotherapy in groups A and B (p < 0.05). There were no complication associated with the treatment process. Conclusions: Using a vaginal dilator in cervical cancer patients after radiotherapy is safe and can effectively promote the recovery of patients’ sexual activity and quality of life.